Crystallization of organic compounds : (Wiley, 2009)
Based on the authors' hands-on experiences as process engineers at Merck, Crystallization of Organic Compounds guides readers through the practical aspects of crystallization. It uses plenty of case studies and examples of crystallization processes, ranging from development through manufacturing scale-up. The book not only emphasizes strategies that have been proven successful, it also helps readers avoid common pitfalls that can render standard procedures unsuccessful.